Overdenture and prosthesis protocol in dentistry: A comprehensive review (International Seven Journal of Multidisciplinary, 2024)
This article comprehensively reviews overdentures and protocol prostheses in dentistry, highlighting their indications, materials used, clinical techniques, and maintenance considerations. The objective is to provide a detailed view of the differences, similarities and technological advances that influence these treatment modalities, based on a critical analysis of recent scientific literature.